Arts and humanities - Rodrigo, Imelda O. (Manila : Edric Publishing House, 2024)
"Arts and humanities are broad fields of study and practice that examine human experience, expression and creativity. Despite their immense diversity, both area share a common focus on understanding the various ways in which people interpret ad document the human condition."
Includes bibliography.
English.
Keywords: Arts and humanities